PENGEMBANGAN METODE OTENTIKASI KEASLIAN IJASAH DENGAN MEMANFAATKAN GAMBAR QR CODE - Eka Ardhianto; Nur Wakhidah (Jurnal Transformatika, 2016)
- QR Code is two-dimensional image that represents the data, particularly data-shaped teks. QR Code is an evolution of the first one-dimensional barcode into two dimentions. QR Code has the ability to store much more data than a barcode.One of the important data in the campus are collegers certificate. It is a document that serves as proof of authenticity that someone has undergone a formal education stage and successfully pass the exam. The collegers certificate conventionally used today is a collegers certificate in physical form so that there is the possibility of lost or damaged. Conventional collegers certificate verification process is difficult because the process is carried out only by the manufacturer of collegers certificate. The means used to verify the authenticity of the data collegers certificate today is to make direct contact to the manufacturer's certificate regarding authenticity certificate holder, as well as the legalization process tertandatangan of collegers certificate maker.From the conduct of research and testing conducted it can be concluded that: QRCode can be used to accommodate large data information of graduate, Facilitate the detection of the authenticity of the certificate of ownership information from mobile devices, also QRCode can be quickly used to verify the certificates quickly and accurately